2019
DOI: 10.12688/f1000research.14856.5
|View full text |Cite
|
Sign up to set email alerts
|

Areca nut extract demonstrated apoptosis-inducing mechanism by increased caspase-3 activities on oral squamous cell carcinoma

Abstract: Background: Oral squamous cell carcinoma is a neoplasm of keratinocyte cells of oral mucosa epithelium that can potentially spread through lymphatic tissue or blood vessel. Although areca nut is one of the plants with a risk of inducing that cancer, areca nut is believed to have high antioxidant properties. Due to the current interest in the apoptosis effects from areca nut for oral cancer treatment, we investigated its ability to induce apoptosis and caspase-3 activity in oral cancer cell lines: HSC-2 and HSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Areca nut, as one of the main ingredients, contains phenolic and flavonoids which function as antioxidants. 19 Catechin is a component of flavonoids present in areca nut that acts as an antioxidant by chelating the ions and scavenging the free radicals particularly, superoxide (O 2-), peroxyl, hydroxyl radicals (ÁOH), and hence inhibit both DNA damage and lipid peroxidation, which can cause membrane damage. 20 Catechin can reduce the expression of interleukin-6 (IL-6) and IL-8 which function to overcome inflammation and increase the wound healing process by chemotactic for fibroblasts, accelerates their migration and stimulates deposition of tenascin, fibronectin, and collagen I during wound healing in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Areca nut, as one of the main ingredients, contains phenolic and flavonoids which function as antioxidants. 19 Catechin is a component of flavonoids present in areca nut that acts as an antioxidant by chelating the ions and scavenging the free radicals particularly, superoxide (O 2-), peroxyl, hydroxyl radicals (ÁOH), and hence inhibit both DNA damage and lipid peroxidation, which can cause membrane damage. 20 Catechin can reduce the expression of interleukin-6 (IL-6) and IL-8 which function to overcome inflammation and increase the wound healing process by chemotactic for fibroblasts, accelerates their migration and stimulates deposition of tenascin, fibronectin, and collagen I during wound healing in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Although its precise role in wound healing is not fully understood, however, (1). [14][15][16][17][18][19] reported that TNF-α is involved in the early process of wound healing. It is quickly released and initiates inflammation at wound tissues.…”
Section: Among All Inflammatory Cytokines Why Tnf-alpha Was Chosen?mentioning
confidence: 99%
“…9 Potency antioxidant activity of areca nut has been well established in the previous in vitro research using several oral cancer cell lines. 10 Although some areca nut products such as paan masala (fennel seeds, coriander, sesame, mint leaves, powdered lime, areca nut, cardamom, and pure menthol) and gutkha (chewing tobacco, dried ripe areca nut, paraffin wax, slaked lime (calcium hydroxide), and savory or sweet flavorings) have contribution in pathogenesis of oral squamous cell carcinoma (OSCC), several other studies have been carried out to prove the efficacy and safety of areca nuts depending on the type of phytochemical content possessed by the areca nut species from the certain region.…”
Section: Introductionmentioning
confidence: 99%
“…4 Potency antioxidant activity of areca nut has been well established in the previous in vitro research using several oral cancer cell lines. 5 Although some areca nut products such as paan masala (fennel seeds, coriander, sesame, mint leaves, powdered lime, areca nut, cardamom, and pure menthol) and gutkha (chewing tobacco, dried ripe areca nut, paraffin wax, slaked lime (calcium hydroxide), and savory or sweet flavorings) have contribution in pathogenesis of oral squamous cell carcinoma (OSCC), several other studies have been carried out to prove the efficacy and safety of areca nuts depending on the type of phytochemical content possessed by the areca nut species from the certain region.…”
Section: Introductionmentioning
confidence: 99%